2017
DOI: 10.1371/journal.pone.0186697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic control and type of diabetes treatment on unsuccessful TB treatment outcomes among people with TB-Diabetes: A systematic review

Abstract: BackgroundStringent glycemic control by using insulin as a replacement or in addition to oral hypoglycemic agents (OHAs) has been recommended for people with tuberculosis and diabetes mellitus (TB-DM). This systematic review (PROSPERO 2016:CRD42016039101) analyses whether this improves TB treatment outcomes.ObjectivesAmong people with drug-susceptible TB and DM on anti-TB treatment, to determine the effect of i) glycemic control (stringent or less stringent) compared to poor glycemic control and ii) insulin (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
(50 reference statements)
1
42
0
Order By: Relevance
“…This need for evidence is supported by the potential benefit of treating diabetes and improving glycaemic control on tuberculosis treat ment outcomes. [3][4][5] This study should, however, be interpreted in the con text of some drawbacks. First, we included 200 studies among which 81 (41%) and 31 (16%) had a moderate and high risk of bias, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This need for evidence is supported by the potential benefit of treating diabetes and improving glycaemic control on tuberculosis treat ment outcomes. [3][4][5] This study should, however, be interpreted in the con text of some drawbacks. First, we included 200 studies among which 81 (41%) and 31 (16%) had a moderate and high risk of bias, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…2 Diabetes triples the risk of developing tuberculosis, and poor glycaemic control adversely affects tuberculosis treatment outcomes with effects such as prolongation of culture conversion, treatment failure, relapse, and death. [3][4][5] Furthermore, diabetes accounted for 10·6% of global tuberculosis deaths among HIVnegative individuals in 2015. 6 With 425 million people affected by diabetes globally in 2017, and a predicted 48% increase up to 629 million people who would have diabetes in 2045, it is foreseeable that this surge in the prevalence of diabetes will contribute to increase the incidence of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of the effect of diabetes on TB treatment outcomes found that patients with diabetes had approximately twice the odds of death (pooled odds ratio [OR] 2.1, 95% confidence interval [CI] 1.8–2.5) and TB relapse (pooled OR 1.8, 95% CI 1.4–2.3) compared to patients without diabetes [56]. However, the majority of studies that estimated an association between diabetes and adverse TB outcomes did not stratify by previously diagnosed diabetes, undiagnosed pre-existing diabetes, or extent of hyperglycemia, and none have estimated the effect of stress hyperglycemia on TB treatment outcomes [57]. …”
Section: Section 3: Implications Of Stress Hyperglycemia On Tb Treatmmentioning
confidence: 99%
“…Another study from Peru that measured diabetes medication use among 136 patients with TB and diabetes reported the highest risk of poor TB outcome among those receiving only insulin (38%) during TB treatment as compared to those receiving oral hypoglycemic agents (14%) or both (12%) [60]. Overall, studies that estimated the effects of glycemic levels on TB outcomes have heterogeneous results [57], likely due to the timing of glucose levels measurements, severity of TB disease at baseline, type of diabetes care, and the complex amalgamation of patients with TB and previously diagnosed diabetes, undiagnosed pre-existing diabetes, and stress hyperglycemia.…”
Section: Section 3: Implications Of Stress Hyperglycemia On Tb Treatmmentioning
confidence: 99%
“…A recent systematic review showed that glycaemic control has a favourable effect on TB treatment outcomes and, conversely, uncontrolled DM or poor glycaemic control (i.e. HbA1c > 7%) was associated with delayed sputum conversion …”
Section: Introductionmentioning
confidence: 99%